USING DUOLINGO APPS TO IMPROVE ENGLISH READING COMPREHENSION OF ENGINEERING STUDENTS IN UNIVERSITAS BORNEO TARAKAN - Pangkuh Ajisoko (Universitas Muhammadiyah Makassar, 2022)
Learning English is matter of learning language components and language skills. Reading is the most difficult learning that plays important role in mastering English Language. Learning reading is quite challenging. It needs various techniques and applications. The transformation of English language learning is mostly affected by technological advances. The development of English Language Teaching (ELT) resources, Duolingo participates to transform method of English language learning on smartphone. The aim of this study is to find out the impact of Duolingo in ELT as extensive learning. Pre-experimental design with pre-test and post-test was used in this research. The researcher involved 15 students as sample with 2 months practicing duolingo apps with 20 xp on each day intensity of practice. The researcher used reading tests as pre-test and post-test and questionnaire to see students’ perception. According to the results, there was massive improvement on students score. Students also felt that Duolingo is useful apps to use everyday to learn English.